2013
DOI: 10.1073/pnas.1309378110
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Interferon Regulatory Factor 4 is required for the generation of protective effector CD8 + T cells

Abstract: Robust cytotoxic CD8 + T-cell response is important for immunity to intracellular pathogens. Here, we show that the transcription factor IFN Regulatory Factor 4 (IRF4) is crucial for the protective CD8 + T-cell response to the intracellular bacterium Listeria monocytogenes. IRF4-deficient (Irf4 −/− ) mice could not clear L. monocytogenes infection and generated decreased numbers of L. monocytogenesspecific CD8 + T cells with impaired effector phenotype and function. Transfer of wild-type CD8 + T cells into Irf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 38 publications
10
85
0
Order By: Relevance
“…Whereas T-bet (Intlekofer et al 2005;Joshi et al 2007), Id2 (Cannarile et al 2006), Blimp-1 (Kallies et al 2009;Rutishauser et al 2009) and interferon regulatory factor (IRF)4 (Man et al 2013;Raczkowski et al 2013;Yao et al 2013) promote effector development, BCL-6 (Cui et al 2011;Ichii et al 2002), Eomesodermin (Eomes) (Intlekofer et al 2005), Id3 (Ji et al 2011;Yang et al 2011), TCF-7 (Zhou et al 2010) and Foxo1 (Hess Michelini et al 2013Kim et al 2013;Tejera et al 2013) are associated with memory-cell differentiation. Several signaling pathways induced by environmental cues regulate the expression of these transcriptional regulators.…”
Section: Transcriptional Regulation Of Effector and Memory Tc1 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas T-bet (Intlekofer et al 2005;Joshi et al 2007), Id2 (Cannarile et al 2006), Blimp-1 (Kallies et al 2009;Rutishauser et al 2009) and interferon regulatory factor (IRF)4 (Man et al 2013;Raczkowski et al 2013;Yao et al 2013) promote effector development, BCL-6 (Cui et al 2011;Ichii et al 2002), Eomesodermin (Eomes) (Intlekofer et al 2005), Id3 (Ji et al 2011;Yang et al 2011), TCF-7 (Zhou et al 2010) and Foxo1 (Hess Michelini et al 2013Kim et al 2013;Tejera et al 2013) are associated with memory-cell differentiation. Several signaling pathways induced by environmental cues regulate the expression of these transcriptional regulators.…”
Section: Transcriptional Regulation Of Effector and Memory Tc1 Cellsmentioning
confidence: 99%
“…Finally, the strength of T cell receptor (TCR) signaling plays pivotal role for differentiation of effector Tc1 cells and the transcription factor IRF4 was recently shown to be the central sensor translating signal strength into a transcriptional program (Man et al 2013;Raczkowski et al 2013;Yao et al 2013). Strong TCR signaling causes high expression of IRF4, while weak signals induce lower amounts of this transcription factor.…”
Section: Transcriptional Regulation Of Effector and Memory Tc1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, studies have suggested that IRF4, together with BATF (basic leucine zipper transcription factor ATF-like) and the activator protein-1 family member JUN, acts as a 'pioneer transcriptional factor' that prepares chromatin accessibility for the subsequent lineage-specific transcriptional factor and drives gene expression for the differentiation of effector T cells [8][9][10]. It has been documented that IRF4 is necessary for the differentiation of diverse effector CD4 + T cell subsets, including helper T cell (Th) types 2 [11][12][13], Th9 [14] and Th17 [6,15,16], follicular Th cells [17], the sustained effector function of cytotoxic T cells [18][19][20], the regulation of effector regulatory T cells (Tregs) [21], the series of developmental stages of B cells [17,[22][23][24][25][26] and the development and function of dendritic cells (DCs) [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that IRF4 is essential for sustaining the differentiation of CD8 + T cells by regulating transcriptional factors that are crucial for effector generation (T-bet and Blimp-1) [18,19]. Furthermore, the expression of IRF4, which is regulated by antigen-T cell receptor (TCR) affinity, has also been reported to be required for the metabolic function and migratory behaviour of activated CD8 + T cells in a dose-dependent manner [20].…”
Section: Introductionmentioning
confidence: 99%